Information on organic farming - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
The Henry Doubleday Research Association (HDRA) is primarily an association of British gardeners and farmers who practise organic cultivation, and is a registered charity. It conducts research into improved, ecologically sound, and sustainable...